Ensayo de una «anatomía» de la República de las Letras. Nueva España, siglo XVIII - Moreno Gamboa, Olivia (2019)
This article draws on old and recent concepts from cultural and literary history as applied to the Republic of Letters in pre-revolutionary France, transferring them to the history of New Spain, with the goal of tracing the “anatomy” or social and professional profile of Mexican authors. During the 18th century, this community experienced important changes in its composition, related to some extent to ecclesiastical secularization and the Bourbon Reforms. This article seeks to contribute to the debate on the impact of the Enlightenment on colonial Spanish America.